Europa e Italia. Studi in onore di Giorgio Chittolini / Europe and Italy. Studies in honour of Giorgio Chittolini - scientifico Reti medievali, Comitato (Reti Medievali E-Book, 2011)
With this collection of studies, the Reti Medievali editorial team intends to honour a maestro who, through the example of his research and his constant openness to discussion and debate, showed an entire generation of Italian historians the importance of a watchful regard towards comparison and contact with the international scientific community of medieval and modern age scholars.